Globalization and the Concentration of Talent - Ulrich Schetter; Oriol Tejada (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We analyze the allocation of talent across teams in large matching markets with competition for rank. We show that under general conditions globalization in the form of a convex transformation of payoffs promotes the concentration of talent, i.e. it makes positive assortative matching more likely and negative assortative matching less likely. This is in line with recent trends in European football (soccer) leagues.
Keywords: D00; D02; D3; D4; D62; D85; J01; P40; Z2; 330; globalization; inequality; matching; rank competition; strategic interaction